Photofunctional Co-Cr Alloy Generating Reactive Oxygen Species for Photodynamic Applications. (3rd April 2013) - Wang, Kang-Kyun; Kim, Bong-Jin; Lee, Mi Hee; Kwon, Byeong-Ju; Choi, Dong Hoon; Park, Jong-Chul; Kim, Yong-Rok
Abstract : We report the fabrication of photofunctional Co-Cr alloy plate that is prepared by a simple modification process for photodynamic application. Photoinduced functionality is provided by the photosensitizer of hematoporphyrin (Hp) that initially generates reactive oxygen species (ROS) such as superoxide anion radical and singlet oxygen. The photosensitizer with carboxyl group was chemically bonded to the surface of the Co-Cr alloy plate by esterification reaction. Microstructure and elemental composition of the Co-Cr alloy plate were checked with scanning electron microscopy (SEM) and energy dispersive X-ray spectrometer (EDS). Fabrication of the photofunctionality of the Co-Cr alloy plate was confirmed with X-ray photoelectron spectroscopy (XPS), reflectance UV-Vis absorption, and emission spectroscopy. Reactive oxygen generation from the photofunctional Co-Cr alloy plate was confirmed by using the decomposition reaction of 1, 3-diphenylisobenzofuran (DPBF). The results suggest that the immobilized photosensitizer molecules on the surface of Co-Cr alloy plate still possess their optical and functional properties including reactive oxygen generation. To open the possibility for its application as a photodynamic material to biological system, the fabricated photofunctional Co-Cr alloy is applied to the decomposition of smooth muscle cells.